Water droplet mobility on a hydrophobic surface under a thermal radiative heating. (5th January 2018) - Al-Sharafi, Abdullah; Yilbas, Bekir S.; Ali, Haider
Highlights: Bond number remains less than unity for all volumes of droplet considered on hydrophobic surface. Combination of Marangoni and buoyancy currents generates fluid acceleration causing droplet roll off. Fluid inertia force remains higher than adhesion and shear forces at droplet solid surface interface. Nusselt and the Bond numbers increases with increasing droplet volume. Abstract: Side heating of a water droplet on the hydrophobic surface is considered and the droplet internal fluidity is examined. An experiment is carried out to assess the droplet mobility on the hydrophobic surface when subjected to the heating load. Temperature and flow fields are simulated in line with the experimental conditions and fluid acceleration inside the droplet is predicted for various droplet sizes. Predictions of the flow field are validated via particle image velocimetry (PIV) measurements. The adhesion, inertia, and shear forces are determined for possible rolling off the droplet on the hydrophobic surface. The Bond and the Nusselt numbers are predicted and the influence of the droplet size on the Bond and Nusselt numbers are presented. It is found that the velocity predictions agree well with the PIV data. Two counter rotating circulation cells are formed inside the droplet due to the combination of the Marangoni and buoyancy currents. The Bond number remains less than unity (in the range 0.03–0.2) for all the droplet sizes incorporated in the study (15–100 μL). This indicates that the Marangoni current dominates over the buoyancy current inside the droplet. The droplet fluid inertia force becomes greater than the adhesion and the fluid shear forces during the heating period; consequently, the droplet rolls off on the hydrophobic surface, which is also observed from the experiments. The Nusselt and the Bond Numbers increase with increasing droplet volume and reach maximum of 151 and 0.2 for the droplet size of 100 μL.